Soil carbon stocks in planted woodlots and Ngitili systems in Shinyanga, Tanzania - Osei, A.; Kimaro, Anthony A.; Peak, D.; Gillespie, Adam W.; VanRees, K. (Springer, 2017)
The authors gratefully acknowledge financial support from the University of Saskatchewan as tuition for the first author and the Natural Science and Engineering Research Council of Canada (NSERC) via the strategic grant from Dr. Vic Timmer for the woodlot research in Tanzania. Also, extra thanks go to Drs. Ken Van Rees and Derek Peak for providing additional funds towards the first author’s studies. Technical support from Richard Farrell at the Soil Science Department, University of Saskatchewan is greatly appreciated and also to the Soil Science Department University of Saskatchewan; World Agroforestry Centre, Dar es Salaam-Tanzania; Natural Forest Resources Management and Agroforestry Centre (NAFRAC), Shinyanga and Dr. Robert Otsyina at Development Associates, Tanzania. Research described in this paper was performed at the Canadian Light Source, which is supported by the Canadian Foundation for Innovation, Natural Sciences and Engineering Research Council of Canada, the University of Saskatchewan, the Government of Saskatchewan, Western Economic Diversification Canada, the National Research Council Canada, and the Canadian Institutes of Health Research.